2019
DOI: 10.11114/jets.v7i2.3767
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Relationship Between the Leisure and Stepping Frequencies of the Students Receiving Recreation Education

Abstract: The simplest and easiest type of physical activity for a healthy individual is walking. Development of technology day by day brought along inactivity and related diseases. The purpose of exercise is to prevent and slow down diseases caused by a sedentary lifestyle. The aim of the study is to reveal the effect of walking on body composition of the individual and to investigate the relationship between the stepping frequency before and after taking a recreation course of the students studying at the faculty of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As supported by the results of this research in the literature, activities that increase recreational awareness contribute to increasing physical activity levels and making them planned and programmed. Another study examined the correlation between recreation and stepping frequencies among the university students who completed recreation education and suggested that stepping frequency went up and an awareness was raised after the recreation education according to correlation analysis (Alpullu and Demir, 2019). The results of this research will contribute to the fact that experts in the field of recreation make some educational programmes that increase awareness of recreational benefits in university students.…”
Section: Discussionmentioning
confidence: 88%
“…As supported by the results of this research in the literature, activities that increase recreational awareness contribute to increasing physical activity levels and making them planned and programmed. Another study examined the correlation between recreation and stepping frequencies among the university students who completed recreation education and suggested that stepping frequency went up and an awareness was raised after the recreation education according to correlation analysis (Alpullu and Demir, 2019). The results of this research will contribute to the fact that experts in the field of recreation make some educational programmes that increase awareness of recreational benefits in university students.…”
Section: Discussionmentioning
confidence: 88%